Corn hybrid performance under the action of Pratylenchus brachyurus and P. zeae - Neves, Samira Scaff [UNESP]; Martins Soares, Pedro Luiz [UNESP]; Paula Batista, Elder Simoes de [UNESP]; Santos, Jaime Maia dos [UNESP] (Organization Trop Amer Nematologists, 2016)
Root lesion nematodes (RLN, Pratylenchus spp.) are found in several crops including corn (Zea mays). The aim of this study was to evaluate corn hybrids under the action of two RLN species (Pratylenchus brachyurus and P. zeae), and to study the development of the populations of the nematodes on corn. The assay was conducted in a greenhouse with six corn hybrids (DKB390 PRO, DKB350 PRO, DKB250 PRO, AS1572 PRO, AG8061 PRO, and an Experimental Hybrid). We found that P. zeae populations increased more than P. brachyurus populations in all the hybrids, but P. brachyurus was more harmful to the development of the plants. Although all the hybrids allowed the multiplication of the nematodes, they differed in their response. Fresh leaf mass and P. brachyurus multiplication were higher in the hybrid AG8061 PRO. Based on these results, it is not possible to assume that these hybrids are resistant to RLN, but they may possess a source of resistance to the RLN in their background.
Keywords: root lesion nematodes; genotypes; Zea mays